FACTORS OF DEVELOPMENT OF PEDAGOGICAL CULTURE IN STUDENTS IN THE FIELD OF SPORTS - Umarov Karim Sadullayevich (Bright Mind Publishing, 2025)
This article analyzes the development of pedagogical culture of students in the field of sports, the structure and levels of pedagogical culture, the main requirements for a modern teacher. It also discusses the issue of the fact that the effectiveness of a teacher's professional activity depends not only on knowledge and skills, but also on the ability to use the information provided in a pedagogical situation in various ways and quickly.
Keywords: Culture, competence, sports pedagogy, method, approach, development.